Developing coding skills: technology for a flipped classroom - Martins, Ciro (2018)
Knowing how to code is critical nowadays, and coding skills are treasured in a growing range of diversified areas. This led to the emerging of several learning platforms that allow students with different kind of knowledge to develop their coding skills. These platforms provide active and fun ways to learn how to code, using technology to create controlled, practical learning and teaching experiences both for students and teachers. The whole idea of this work is to depict a teaching and learning strategy based on the assumption that the use of technology leads students to a greater engagement in learning activities and promotes student–teacher interaction, as well as on the advantages of using an innovative approach to learning, i.e. flipped classrooms.